New Insights into the Role of the Immune Microenvironment in Breast Carcinoma - Luis de la Cruz-Merino; Antonio Barco-Sánchez; Fernando Henao Carrasco; Esteban Nogales Fernández; Ana Vallejo Benítez; Javier Brugal Molina; Antonio Martínez Peinado; Ana Grueso López; Manuel Ruiz Borrego; Manuel Codes Manuel de Villena; Víctor Sánchez-Margalet; Adoración Nieto-García; et al. (Clinical and Developmental Immunology)
Recently, immune edition has been recognized as a new hallmark of cancer. In this respect, some clinical trials in breast cancer have reported imppressive outcomes related to laboratory immune findings, especially in the neoadjuvant and metastatic setting. Infiltration by tumor infiltrating lymphocytes (TIL) and their subtypes, tumor-associated macrophages (TAM) and myeloid-derived suppressive cells (MDSC) seem bona fide prognostic and even predictive biomarkers, that will eventually be incorporated into diagnostic and therapeutic algorithms of breast cancer. In addition, the complex interaction of costimulatory and coinhibitory molecules on the immune synapse and the different signals that they may exert represent another exciting field to explore. In this review we try to summarize and elucidate these new concepts and knowledge from a translational perspective focusing on breast cancer, paying special attention to those aspects that might have more significance in clinical practice and could be useful to design successful therapeutic strategies in the future.